2007
DOI: 10.1111/j.1752-7325.2007.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic Restorative Treatment and Dental Anxiety in Outpatients Attending Public Oral Health Clinics in South Africa

Abstract: The first hypothesis was accepted; the second, rejected. Although dental anxiety scores were lower both in child and in adult patients treated by ART than in those who received traditional restorative treatments, this positive effect had not resulted in higher restoration/extraction ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 14 publications
1
37
0
6
Order By: Relevance
“…While two studies of 6-7-year-old children have found no difference in anxiety between children undergoing ART and those undergoing traditional restorative treatment for caries, 128,129 a study of children and adults in South Africa concluded that ART leads to lower dental anxiety in contrast to traditional restorative techniques. 130 Similarly, while one review of the literature on ART suggests 'that it is a suitable approach to be used in children, the elderly, special needs patients, or patients who demonstrate fear and anxiety towards dental treatment' (p. e672), 131 another review concludes that the association between different restorative procedures and dental anxiety, pain and discomfort is contradictory and requires further investigation. 132 For people who feel anxiety in relation to the noise, vibration, discomfort or pain of a standard rotary drill, air abrasion offers another worthwhile alternative.…”
Section: Alternative Methods For Tooth Preparationmentioning
confidence: 99%
“…While two studies of 6-7-year-old children have found no difference in anxiety between children undergoing ART and those undergoing traditional restorative treatment for caries, 128,129 a study of children and adults in South Africa concluded that ART leads to lower dental anxiety in contrast to traditional restorative techniques. 130 Similarly, while one review of the literature on ART suggests 'that it is a suitable approach to be used in children, the elderly, special needs patients, or patients who demonstrate fear and anxiety towards dental treatment' (p. e672), 131 another review concludes that the association between different restorative procedures and dental anxiety, pain and discomfort is contradictory and requires further investigation. 132 For people who feel anxiety in relation to the noise, vibration, discomfort or pain of a standard rotary drill, air abrasion offers another worthwhile alternative.…”
Section: Alternative Methods For Tooth Preparationmentioning
confidence: 99%
“…One hundred and twenty references were found in MEDLINE, using the term atraumatic restorative treatment. Amongst the references found, a total of 17 were selected: 4 were review of literature and 13 were research studies (1,3,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The 13 research studies are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The authors considered relevant its "less traumatic" aspect, especially for children who suffer from fear of dental treatment. In South Africa, children and adults, who were submitted to the atraumatic restorative treatment, showed significantly lower levels of anxiety than individuals who underwent conventional treatment (18,19). Furthermore, when 518 children who needed class II restorations were treated by three kinds of caries removal method (traditional, ART and chemical-mechanic methods), no significant differences were found in the anxiety levels between the groups.…”
Section: Klinbergmentioning
confidence: 95%
“…A partir do advento da mínima intervenção na Odontologia, as lesões diagnosticadas precocemente começaram a receber tratamentos não invasivos envolvendo condutas de paralisação e controle 9 . As abordagens não invasivas são vantajosas em crianças, pois, além de preservarem tecidos dentais saudáveis, são mais rápidas e de baixo custo [10][11] . Os selantes resinosos de fóssulas e fissuras foram desenvolvidos com finalidade preventiva, sendo aplicados sobre a face oclusal de dentes suscetíveis ao desenvolvimento de lesões de cárie, formando uma barreira mecânica que impede a retenção de restos alimentares e a formação de biofilme nas áreas de difícil controle de higiene, prevenindo assim o desenvolvimento da lesão de cárie 6,12 .…”
unclassified